Estradiol mediates the interaction of LINC01541 and miR-429 to promote angiogenesis of G1/G2 endometrioid adenocarcinoma in-vitro: A pilot study - Qiao, Dan; Qin, Xiaoduo; Yang, Haiyan; Liu, Xuantong; Liu, Libing; Liu, Sufen; Jia, Zhongzhi (Frontiers in Oncology, 2022)
Background Endometrioid adenocarcinoma (EAC) is the most common subtype of endometrial cancer (EC) and is an estrogen-related cancer. In this study, we sought to investigate the expressions and mechanism of action of 17β-estradiol (E2) and long noncoding RNA (lncRNA) LINC01541 in G1/G2 EAC samples. Methods The expressions of estrogen receptor β (ESR2), LINC01541, miR-200s, and VEGFA were evaluated using real-time PCR in human EAC tissues (n = 8) and adjacent normal tissues (n = 8). Two EC cell lines (Ishikawa and RL95-2) were selected for validation in vitro. Bioinformatics analyses and luciferase reporter analyses were performed to verify potential binding sites. qRT-PCR, Western blot, and CCK-8 were used to identify the regulatory mechanisms of related genes in cell biological behavior. Results Compared with adjacent normal tissues, LINC01541 and miR-200s family (except miR-200c) were highly expressed in EAC tissues (n=8), while ESR2 and VEGFA were lowly expressed in EAC tissues (* P < 0.05; ** P < 0.01). In vitro: E2 inhibited the expression of LINC01541 and miR-429 in both cell lines, and estrogen antagonist (PHTPP) could reverse this effect, in addition, PHTPP could promote the proliferation of these two cancer cells, cell transfection LINC01541 also had this effect after overexpression of plasmid and miR-429 mimic. E2 promotes the expression of VEGFA in both cell lines, and PHTPP can also reverse this effect. LINC01541 interacts with miR-429 to promote the expression of each other, and both inhibit the synthesis of VEGFA in EAC cells after overexpression. Through the double validation of bioinformatics analysis and dual fluorescein reporter gene, it was confirmed that miR-429 targets the regulation of VEGFA expression (* P < 0.05; ** P < 0.01). Conclusion E2 promotes the synthesis of VEGFA by altering the expression levels of LINC01541 and miR-429 in EAC, thereby affecting the angiogenesis process of EAC. Also, E2-mediated LINC01541/miR-429 expression may affect cell migration in EAC. In addition, we identified a reciprocal promotion between LINC01541 and miR-429.